2015
DOI: 10.1186/s40064-015-1216-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laparoscopic diverted sleeve gastrectomy with ileal transposition (DSIT) on short term diabetic medication costs

Abstract: BackgroundType 2 diabetes mellitus (T2DM) has gained pandemic proportions becoming a global threat within the last few decades. In parallel to the increasing prevalence, healthcare costs have become a huge economic burden for the hospital and governments. Bariatric surgery has been proven to induce glycemic control in obese type 2 diabetics. However, the cost effectiveness of metabolic surgery in overweight, obese and morbidly obese individuals has not been documented. We aimed to demonstrate the efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The procedure was called the ileal transposition, and for the first time, there was a decrease in the amount of food consumed, body weight, glucose, triglycerides, and cholesterol levels with a preserved length of the small intestine [8]. Some clinical studies combined the ileal transposition with gastric bypass surgery or sleeve gastrectomy [33][34][35][36]. During a study of the metabolic effects of the ileal transposition in combination with elevating sleeve gastrectomy (DSG) in 159 patients with obesity and DM2, Celik et al found a decrease in the average body mass index (BMI) from 39.33 to 25.51, the average fasting glucose level from 189.9 to 123.5 mg/dL, and the average HbA1c level from 9.24% to 6.14% a year after surgery [31].…”
Section: Effect Of Bariatric Operations On Glucose Metabolismmentioning
confidence: 99%
“…The procedure was called the ileal transposition, and for the first time, there was a decrease in the amount of food consumed, body weight, glucose, triglycerides, and cholesterol levels with a preserved length of the small intestine [8]. Some clinical studies combined the ileal transposition with gastric bypass surgery or sleeve gastrectomy [33][34][35][36]. During a study of the metabolic effects of the ileal transposition in combination with elevating sleeve gastrectomy (DSG) in 159 patients with obesity and DM2, Celik et al found a decrease in the average body mass index (BMI) from 39.33 to 25.51, the average fasting glucose level from 189.9 to 123.5 mg/dL, and the average HbA1c level from 9.24% to 6.14% a year after surgery [31].…”
Section: Effect Of Bariatric Operations On Glucose Metabolismmentioning
confidence: 99%
“…Редкой причиной смерти животных в послеоперационном периоде может быть ýвентрациявыпадение органов брюшной полости через дефект передней брюшной стенки, обусловленный несостоятельностью хирургического шва послеоперационной раны [37,41]. В случае ýвентрации животное нуждается в ýкстренной операции.…”
Section: особенности послеоперационного периодаunclassified